The Implementation of English Teaching in New Normal Era during Covid-19 Pandemic at SMP Negeri 3 Teras - Hardiyanto, Ocavaro De Adio; Hikmat, Mauly Halwat; Sanjani, Muhammad Iqwan (Jurnal Keilmuan dan Keislaman, 2022)
This research discusses the implementation of English teaching in new normal era during COVID-19 pandemic which reveals the offline teaching activity in class with the new normal health protocol implementation, the procurement of health protocol support facilities, and the students’ preference of learning methods which have been experienced during COVID-19 pandemic. The objectives of this research are: a) providing the portray of English teaching activity and the activity in school in general in new normal era during COVID-19 pandemic, and b) measuring the students’ preference of the used learning methods both offline or online learning in COVID-19 pandemic. The subject of this research was the 7th students and teacher at SMP Negeri 3 Teras. The techniques of collecting data used were observation, interview, and questionnaire. The data from the observation and questionnaire for this research were analyzed qualitatively in order to provide the phenomena in the school descriptively, while the students’ questionnaire responses were also processed qualitatively and provided descriptively. The findings of this research showed that there were a number of differences which were implemented in limited offline learning such as the limitation of class capacity, weekly schedule setting, the implementation of new normal health protocol (wearing mask, limitation of class capacity, and keeping the distance) and providing the facilities which support the prevention of COVID-19 spread such as washstand, hand sanitizer, and thermometer.